2019
DOI: 10.1371/journal.pone.0217397
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pre-gestational and gestational smoking and factors associated with smoking cessation during pregnancy, Brazil, 2011-2012

Abstract: Gestational smoking is associated with various adverse maternal and fetal outcomes. Over the last three decades, despite considerable advances in tobacco control policy in Brazil, gestational smoking has caused a considerable number of fetal deaths and disabilities. The aim of this study is to estimate the prevalence of pre-gestational and gestational smoking and to identify the factors associated with smoking cessation up to the 20 th gestational week. Methods: “Birth in Brazil” was a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 40 publications
1
9
1
1
Order By: Relevance
“…The prevalence found in the present study for smoking was slightly higher than the national average estimated (21) , but similar to another study with data from all over the country (24) , which found 9.6% of pregnant women smoking at some point during pregnancy. Regarding the prevalence found for alcohol consumption, specific studies in different regions of the country, such as Rio Grande do Sul and Rio de Janeiro (25)(26) , found similar results to the present research.…”
Section: Discussionsupporting
confidence: 90%
“…The prevalence found in the present study for smoking was slightly higher than the national average estimated (21) , but similar to another study with data from all over the country (24) , which found 9.6% of pregnant women smoking at some point during pregnancy. Regarding the prevalence found for alcohol consumption, specific studies in different regions of the country, such as Rio Grande do Sul and Rio de Janeiro (25)(26) , found similar results to the present research.…”
Section: Discussionsupporting
confidence: 90%
“…Self-reported maternal information, such as maternal smoking, may be underestimated due to pregnant women's knowledge of harmful effects to mother and child's health. 29 The fact that the condition of an ex-smoker was not considered as a distinct category of maternal smoking, it may have weakened the magnitude of the associations. In addition to self-report on alcohol consumption was measured using TWEAK.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the mother's education and depression classification, the current study looks at other factors which have been studied in relation to prenatal substance use: maternal living arrangement (alone or with someone) [21,23], yearly income [22], and PTSD classification [24]. It also investigates if the education or employment of the father and mother together would alter maternal smoking rates.…”
Section: Factors Studiedmentioning
confidence: 99%
“…Risk factors for alcohol use include depression [21,22], anxiety [21], being unmarried [22], belonging to a lower socioeconomic status [22], and being black [22] or white [20]. Protective factors against smoking during pregnancy include attending one prenatal consult [23], more years of schooling [23], living with a partner [21,23], having no previous children [23], and the absence of alcohol use [23]. Having PTSD [24] or depression [21,25] increases the risk of both alcohol and tobacco use during pregnancy.…”
Section: Introductionmentioning
confidence: 99%